A Curriculum Design Analysis of English Learning Outcomes in Indonesia’s Merdeka Curriculum - Afiya Ulin Nuha Annafiah; Lestari Setyowati; Siti Muniroh (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2026)
This study analyzes the English Learning Outcomes (Capaian Pembelajaran) for junior high school in Indonesia’s Merdeka Curriculum to examine how language competencies are conceptualized and what curriculum design orientation they reflect. While the existing research has largely focused on classroom implementation, limited attention has been given to analyzing the learning outcomes document itself as a curriculum product. Adopting qualitative document analysis, the study examines five competency clauses and the accompanying rationales using the framework of language curriculum development. The findings indicate that the Learning Outcomes document functions primarily as a goals-and-skills specification. Learning content is broadly implied in the outcome statements and elaborated in the rationale, while methodological guidance appears only in the rationale through a genre-based approach. Assessment is not specified within the document but is addressed in separate materials, indicating a fragmented distribution of curriculum information. This pattern reflects a backward design orientation combined with partial methodological direction, revealing a tension between outcome-based flexibility and implicit pedagogical guidance. Also, the Learning Outcomes reflect a predominantly functional view of language, supported by structural elements within a genre-based framework. The curriculum ideology is largely learner-centered, with limited evidence of cultural pluralism and no indication of academic rationalism or social reconstructionism. These findings suggest increased interpretive demands on teachers and highlight the need to strengthen curriculum coherence and teacher curriculum design literacy.